Crosslinking vs. Observation in Fellow Eyes of Keratoconus Patients. (1st June 2022) - Li, Gavin; Di Meglio, Laura; Wang, Jiangxia; Woreta, Fasika A.; Bower, Kraig S.; Jhanji, Vishal; Srikumaran, Divya; Soiberman, Uri S.
Abstract : Purpose . To evaluate whether unilateral crosslinking (CXL) and conservative follow-up of the fellow eye is an acceptable management strategy in patients with keratoconus (KC). Methods . Seventy-nine fellow eyes of KC subjects that initially underwent unilateral CXL were included. Thirty fellow eyes ultimately received CXL (group 1) whereas 49 fellow eyes were followed (group 2). Best spectacle corrected visual acuity (BSCVA) and corneal tomographic parameters were collected in all eyes preoperatively and at the last follow-up. Results . Subjects who received CXL in the fellow eye (group 1) were younger than subjects who did not (group 2, p = 0.026 ). Group 1 eyes had higher baseline K1 (p = 0.026 ), K2 (p = 0.006 ), Km (p = 0.01 ), and Kmax (p = 0.002 ) compared to group 2 eyes. Amongst the 49 naïve fellow eyes (group 2), 19 eyes showed evidence of progression. Progressing naïve eyes had higher baseline K1, K2, Km, and Kmax (p < 0.01 ); progressors also had thinner pachymetry at the pupil, apex, and thinnest point (p < 0.01 ). Baseline values of K1 ≥ 43.5 Diopter (D), K2 > 45.1D, Km > 44.3D, Kmax  > 47.9D, astigmatism > 1.4D, pachymetry at the pupil <475  μ m, and thinnest pachymetry <478  μ m were tentative predictors of progression in the naïve fellow eye. Conclusions . Unilateral CXL with vigilant follow up of the fellow eye may be an acceptable management strategy in a subset of KC eyes.